Effect of Working Gas on the Thermal Stability and Mechanical Property of Hydrogenated DLC Coatings - BI Jun, PENG Ji-hua, LI Lie-jun, ZHOU Feng (Cailiao Baohu, 2021)
In order to reveal the influence of working gas on DLC coating and provide reference for the application of DLC at high temperature, different hydrogen-containing diamond-like carbon films(a-C:H)were prepared on 304 stainless steel substrate by plasma-enhanced chemical vapor deposition(PE-CVD)with different acetylene contents in the working gas(C2H2/Ar flow ratio = 100∶0, 75∶25, 50∶50).The sample was annealed at constant temperature by infrared annealing device, and their friction curves using a ball-disc friction apparatus and microhardness using a microhardness tester in various treatment states were tested.Using a differential thermal analyzer, Raman spectroscopy, infrared spectrum and field emission scanning electron microscopy, the structure of the film was characterized.Results showed that the acetylene content in the working gas affected the surface morphology and growth rate of the DLC coating.As the acetylene content of the working gas decreased, the coating surface tended to be smooth; DLC growth thickness decreased nonlinearly with the decrease of acetylene content in the working gas.Among three coatings with different levels of acetylene(100%, 75%, 50%), the one prepared under 75% acetylene had the lowest sp3 content, but it did not start to increase rapidly until annealing ID/IG above 490 ℃.The hardness of DLC coating prepared by working gas with acetylene content of 75% as prepared and annealed state was higher than that of DLC coating prepared by working gas with acetylene content of 100% and 50%.Under the same pressure, there was no significant change in the friction coefficient of diamond-like films with different C2H2/Ar flow ratios.There was no obvious rule of friction coefficient after annealing at low temperature.Whereas, at higher temperatures(above 490 ℃), the film accelerated the transition from sp3 to sp2 due to high temperature with the formation of a large number of graphite phases, resulting in a decrease in the friction coefficient.